Application of Variable Costing Method to Determine Cost of Production and Selling Price in MSMEs Rengginang 1 Putra, Lumajang Regency - Muhammad Anwarul Putra; Norita Citra Yuliarti; Riyanto Setiawan Suharsono (West Science Accounting and Finance, 2024)
This study aims to examine how the influence and impact of the application of variable costing on the determination of cost of production in Rengginang 1 Putra MSMEs, This study uses a comparative method research case study. This research uses Rengginang 1 Putra MSMEs, which are MSMEs engaged in rengginang production which is precisely located in Karangrejo Village, Yosowilangun District, Lumajang Regency. The types of data used are quantitative data and qualitative data. The results of this study conclude that the application in determining the cost of production in Rengginang 1 Putra MSMEs using the variable costing method is influential in determining the cost of production which only includes variable costs. The application of the variable costing method can provide significant benefits for MSMEs such as Rengginang 1 Putra in determining a more accurate and competitive cost of production. The variable costing method also allows Rengginang 1 Putra MSMEs to be more accurate in calculating the cost of production per unit, because only variable costs are calculated to the product. Thus, Rengginang 1 Putra MSMEs can be more precise in setting product selling prices that are lower than those previously implemented.